Survey of current hand hygiene practices amongst doctors and attitudes on being bare below the elbows - Wan, Wei Yee; Cradle, Bethan (International Journal of Infection Control, 2017)
Compliance with hand hygiene has always been a challenge especially amongst medical staff. There is also a reluctance to be bare below the elbows due to lack of evidence to support this practice. The aim of this survey is to assess doctor’s compliance with hand hygiene and identify barriers faced including evaluation of attitudes and compliance with bare below the elbows. We conducted a doctor and patient survey on current medical staff’s hand hygiene and bare below the elbows practice over a 7 week period. There is generally low compliances to hand hygiene and poor reasons were given to justify this; whilst non-compliance to bare below the elbows were due to the lack of evidence. Arguments are presented to up hold the need for bare below the elbows to facilitate effective hand hygiene practice which is an essential part of patient care to prevent transmission of infections.